Female Sexual Dysfunction in Married Medical Students - Roodsari, Alaleh Asghari; Khademi, Afsaneh; Hamed, Ehsan Akbari; Tabatabaiifar, Seideh Leila; Alleyassin, Ashraf (McGill Journal of Medicine, 2020)
Background: Sexuality and its manifestation constitute some of the most complex of human behavior. Sexual dysfunction is more prevalent in women than in men. Prevalence of the subgroups of female sexual disorders is: desire disorder in 5-46%, arousal disorders in 7-10% and orgasmic disorders in 7- 10%. The objective of our study was to measure the prevalence of female sexual dysfunction in female medical students. Materials and Methods: Thirty two medical students participated in the study. The mean age was 24.30± 1.29 years. Duration of marriage was 2.68±1.5 years. Their husbands’ education ranges from secondary school diploma to PhD. Persian version of Sexual Function Questionnaire (SFQ) was piloted among medical students with and without chief complaint of female sexual dysfunction. Results: Prevalence of an abnormal score in each subgroup of SFQ was as follows: 20.0% in desire, 56.7% in arousal sensation, 33.3% in arousal lubrication, 36.7% in orgasm, 6.7% in pain and 20.0% in enjoyment. In our study 40.0% had sexual problems at least in one subgroup and 6.7% had problems in all subgroups. Only 2 participants were unsatisfied with their sexual life and seeking for any treatment. Discussion: In this study, prevalence of Female Sexual Dysfunction (FSD) ranges from 6.7% to 56.7% in subgroups of the disorder. Solving social problems have critical effect on quality of life. Evaluation of FSD is important in total and especially in women who are university educated and will be occupied in essential positions.